Etiology of oak decline in Spain - Gallego, F J; de Algaba, A Perez; Fernandez-Escobar, R (European Journal of Forest Pathology, 1999)
In different areas of Extremadura, Western Spain, soil samples were taken at the bottom of holm oak (Quercus ilex) trees that were showing decline symptoms. Half of each sample was sterilized, and acorns were sown in both sterilized and nonsterilized soil samples. The resulting seedlings were used as baits for the isolation of fungi. Seedlings growing on the natural, nonsterilized substrate were characterized by having a lower vegetative growth than the ones growing on the sterilized soil samples, and most of them died. Phytophthora dnnamomi was consistently isolated from their roots. Fusarium oxysporum was also isolated as well as different species of Pythium, although to a lesser extent. Pathogenicity tests were performed on holm oak seedlings with five different isolates of P. chinnamomi, with F. oxysporum, Pythium and with a mixture of the three fungi. All the inoculated seedlings with P. chinnamomi developed root rot and grew slowly, and 35.7% of them died up to the end of the experiments. P. chinnamomi was consistently isolated from their roots, indicating that this fungus is the causal agent of holm oak decline. However, F. oxysporum caused similar symptoms on oak seedlings as P. chinnamomi, and was isolated also from the roots, although its frequency was lower than that of. P. cinnamomi.
Keywords: Holm oak; Oak decline; Pathogenicity; Phytophthora cinnamomi (PG)

Etiology of oak decline in Spain - Gallego, F. J.; de Algaba, A. Perez; Fernandez-Escobar, R. (European Journal of Forest Pathology, 1999)
In different areas of Extremadura, Western Spain, soil samples were taken at the bottom of holm oak (Quercus ilex) trees that were showing decline symptoms. Half of each sample was sterilized, and acorns were sown in both sterilized and nonsterilized soil samples. The resulting seedlings were used as baits for the isolation of fungi. Seedlings growing on the natural, nonsterilized substrate were characterized by having a lower vegetative growth than the ones growing on the sterilized soil samples, and most of them died. Phytophthora dnnamomi was consistently isolated from their roots. Fusarium oxysporum was also isolated as well as different species of Pythium, although to a lesser extent. Pathogenicity tests were performed on holm oak seedlings with five different isolates of P. chinnamomi, with F. oxysporum, Pythium and with a mixture of the three fungi. All the inoculated seedlings with P. chinnamomi developed root rot and grew slowly, and 35.7% of them died up to the end of the experiments. P. chinnamomi was consistently isolated from their roots, indicating that this fungus is the causal agent of holm oak decline. However, F. oxysporum caused similar symptoms on oak seedlings as P. chinnamomi, and was isolated also from the roots, although its frequency was lower than that of. P. cinnamomi.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Holm oak; Oak decline; Pathogenicity; Phytophthora cinnamomi (PG)

Sintomas de estres hidrico y DE "SECA" EN ENCINAS (Quercus ilex subsp. ballota) INOCULADAS CON Phytophthora cinnamomi EN UNA DEHESA DEL CENTRO DE ESPAÑA - TUSET, JUAN J; HINAREJOS, C; MIRA, J L; COBOS, J M (II Congreso Forestal Español, 1997)
Phytophthora cinnamomi is a causal agent for the "seca" (oak decline) of the Mediterranean Quercus. The disease symptoms consist basically of a decay of the trees canopy that may occur as a slow decline: gradualleaves fall and presence of partially or totally defoliated branches, or as a quick decline: rapid decline of branches, leaves remaining attached sorne time, and dead trees. There may also be blackish gummose exudates on trunk and main branches. The "seca" reached epidemic rates in the various evergreen oaks or cork oaks distributed on Andalusia, Castilla-La Mancha and Extremadura since 1990-91. From then in the soils of these forestry areas and on feeder roots of cork oaks and evergreen oaks, P. cinnamomi were isolated along the climatological seasons until now. The continued presence of the fungi has lead to determine the susceptibility of Q. ilex subsp. hallota on adult trees in the field. Adult evergreen oak plants were inoculated with young mycelium of P. cinnamomi at La Iglesuela (Toledo) in spring, 1994. At two years, the development of this fungus on roots, trunks and branches of evergreen oak:, shows a great pathogenic capacity and it has achieved the reproduction of clear symptoms of "seca"
Keywords: canker; oak: decline; Pathogenicity; phytophthora cinnamomi; Quercus ¡lex subsp. ballota

Vegetative compatibility and pathogenicity of Diplodia mutila isolates on oak - Ragazzi, A. (European journal of forest pathology, 1997)
Forty isolates of Diplodia mutila, a dieback agent on oaks were characterized by their capacity to produce heterokaryons, by their vegetative compatibility, and by their pathogenicity tests on Quercus cerris. The forty isolates were collected from Quercus cerris, Quercus frainetto, Quercus ilex, Quercus pubescens, Quercus robur and Quercus suber in different regions in Italy. Three nit mutants (nit,, nit, and nit,) were identified with different nitrogen sources: sodium nitrite, sodium nitrate, uric acid, ammonium tartrate and hypoxanthine. O n the two nutrient media employed, a potato dextrose agar (PDA) medium with chlorate (PDC), and a minimal agar medium with chlorate (MMC), isolates obtained from Q. cerris Felded the greatest number of mutants: 254 on PDC (out of a total of 583) and 190 on MMC (out o a total of 440). Nine vegetative compatibility grou s (VCGs) were identified. There was a strong association between these VCGs and host species. Alfisolates tested except one from Q. cerris were pathogenic.
Keywords: diplodia mutila; disease (voyant); nit mutants; Pathogenicity; Quercus; vegetative compatibility